Global trends in research on MOG antibody-associated disease: bibliometrics and visualization analysis - Zheng, Shuhan; Wang, Yang; Geng, Jiaming; Liu, Xueyan; Huo, Liang (Frontiers in Immunology, 2024)
The purpose of this study was to investigate the current research status, focus areas, and developmental trends in the field of Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) through an analysis of scientific literature. Methods:The relevant research articles on MOGAD published from 1947 to 2022 were retrieved from the Web of Science database. The quantitative output of MOGAD related research articles, their distribution by country/region, data on collaborative publishing, influential authors, high-yield institutions, keywords, hotspots, and development trends were analyzed.Additionally, visual knowledge maps were generated using VOSviewer and Citespace.Results: There has been a steady increase in the number of MOGAD related publications indicating that the subject has garnered increasing interest among researchers globally. The United States has been the leading contributor with 496 papers (19.25%), followed by China (244, 9.63%), Japan (183, 7.10%), the United Kingdom (154, 5.98%), and Germany (149, 5.78%). Among these countries, the United Kingdom boasts the highest citation frequency at the rate of 46.49 times per paper. Furthermore, active collaboration in MOGAD related research is observed primarily between the United States and countries such as Canada, Germany, Australia, Italy, the United Kingdom and Japan. Mayo Clinic ranks first in total articles published ( 109) and frequency of citations per article (77.79). Takahashi Toshiyuki from Tohoku University is the most prolific author, while Multiple Sclerosis and Related Disorders is the most widely read journal in this field. "Disease Phenotype", "Treatment", "Novel Coronavirus Infection and Vaccination", "Immunopathological Mechanisms", "Clinical characteristics of children" and "Prognosis" are the primary keywords clusters in this field. "Novel Coronavirus Infection and Vaccination" and "Immunopathological Mechanisms" are research hotspots and have great development potential. Conclusion: The past three decades have witnessed a significant expansion of research on MOGAD. The pathogenetic mechanism of MOGAD is poised to be the prominent research focus in this field in the foreseeable future.